RESISTANCE OF SACCHARUM SPP. AGAINST CHILO SACCHARIPHAGUS INDICUS (KAPUR) (LEPIDOPTERA: CRAMBIDAE) IN INDIA. (28th October 2016) - MAHESH, P.; SRIKANTH, J.; CHANDRAN, K.; SINGARAVELU, B.
SUMMARY: Accessions of four Saccharum spp. from the world collection of sugarcane germplasm maintained at the ICAR-Sugarcane Breeding Institute Research Center, Kannur, Kerala State, India, were screened against Chilo sacchariphagus indicus (Kapur) (Lepidoptera: Crambidae), commonly known as internode borer. Observations on the progression of borer attack in the most susceptible Saccharum officinarum indicated that the incidence began in the first fortnight of July, increased in the next 2 months and reached its peak in September. Thereafter, the incidence decreased in the next 2 months but reached its overall peak in December. Simple correlation coefficients between mean monthly weather parameters and borer incidence were not significant. Percent of canes attacked was significantly lower in 2011 than in 2012 for S. officinarum, Saccharum barberi and Saccharum sinense but did not differ between the years for Saccharum robustum . Amongst the four Saccharum spp., S. robustum showed the lowest borer incidence whereas S. officinarum recorded the lowest attack intensity. Whilst infestation index showed the same trend as percent canes attacked, percent deadhearts did not differ amongst the four Saccharum spp. Considering the 171 accessions evaluated, 29 (16.9%) accessions were resistant, 39 (22.8%) moderately resistant and 103 (60.2%) susceptible to internode borer. Out of the 39 accessions of S. officinarum, none occupied the resistant category whereas 17.9% were in the moderately resistant category. In S. robustum, whilst nearly half (44.5%) the accessions emerged as resistant, a considerable number occupied the moderately resistant category. In S. barberi, no accession was resistant to the borer. In S. sinense, only one accession each represented resistant and moderately resistant categories. Plant morphological characters, yield and quality parameters did not show clear-cut relationship with the three infestation parameters.